MACROECONOMIC FUNDAMENTALS ON THE FINANCIAL PERFORMANCE OF NAIROBI SECURITIES EXCHANGE - Munyao, Deborah M. (International Journal of Economics, 2017)
Purpose: The purpose of this study was to evaluate macroeconomic fundamentals on the financial performance of Nairobi securities exchange. Methodology:Descriptive research design was used to obtain information for this study.The study population consisted of 56 companies listed in the NSE as at July 2012.The study used self-developed structured and unstructured questionnaires which were administered to finance managers in the companies listed under NSE.The study used primary data on the NSE 20-share index, 91-day Treasury bill rate, inflation and exchange rateComputer application packages such as Statistical Package for Social Sciences (SPSS) was used to assist in the analysis and communication of data. Results:The long-run model results indicated that only inflation rate was negatively and significantly related to NSE index. This implied that an increase in inflation rate led to decrease in NSE index. It was concluded that short-run interest rate, inflation rate and GDP were found to be negatively related to short run NSE index. Therefore, an increase in short run interest rate, inflation rate and GDP led to a decrease in short run NSE index. It was concluded that the error correction term LAGRESID has the expected sign and is significantly negative. This result implies that there is a negative gradual adjustment (convergence) to the long run equilibrium. The coefficient indicates that the disequilibria in short run NSE index achieved in one period are corrected in the subsequent period. Policy recommendation: Based on the findings of the study, the study presents recommendations pertinent to the policy makers, investors, financial market regulators and future researchers. The study recommends the government through its policy makers should come up with policies that will help stabilize Foreign exchange rate, Interest rate and Inflation rate fluctuation thus creating investor confidence in the securities market. This will have a significant impact on the performance of the Nairobi Securities Exchange thus foster economic growth.